Tracheotomy in a High‐Volume Center During the COVID‐19 Pandemic: Evaluating the Surgeon's Risk. (1st September 2020) - Thal, Arielle G; Schiff, Bradley A.; Ahmed, Yasmina; Cao, Angela; Mo, Allen; Mehta, Vikas; Smith, Richard V.; Cohen, Hillel W.; Ow, Thomas J.
Abstract : Objective: Performing tracheotomy in patients with COVID‐19 carries a risk of transmission to the surgical team due to potential viral particle aerosolization. Few studies have reported transmission rates to tracheotomy surgeons. We describe our safety practices and the transmission rate to our surgical team after performing tracheotomy on patients with COVID‐19 during the peak of the pandemic at a US epicenter. Study Design: Retrospective cohort study. Setting: Tertiary academic hospital. Methods: Tracheotomy procedures for patients with COVID‐19 that were performed April 15 to May 28, 2020, were reviewed, with a focus on the surgical providers involved. Methods of provider protection were recorded. Provider health status was the main outcome measure. Results: Thirty‐six open tracheotomies were performed, amounting to 65 surgical provider exposures, and 30 (83.3%) procedures were performed at bedside. The mean time to tracheotomy from hospital admission for SARS‐CoV‐2 symptoms was 31 days, and the mean time to intubation was 24 days. Standard personal protective equipment, according to Centers for Disease Control and Prevention, was worn for each case. Powered air‐purifying respirators were not used. None of the surgical providers involved in tracheotomy for patients with COVID‐19 demonstrated positive antibody seroconversion or developed SARS‐CoV‐2–related symptoms to date. Conclusion: Tracheotomy for patients with COVID‐19 can be done with minimal risk to the surgical providers when standard personal protective equipment is used (surgical gown, gloves, eye protection, hair cap, and N95 mask). Whether timing of tracheotomy following onset of symptoms affects the risk of transmission needs further study.